DEWAN DIREKSI DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN - Reva Amrilia; Aminar Sutra Dewi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
Financial performance is a picture of the company's condition to find out whether the company's financial condition is good or bad which reflects the performance of a certain period. This study aims to determine and analyze the influence of board of directors and institutional ownership variables on financial performance in manufacturing companies. The data processed is secondary data from the annual reports of 30 manufacturing companies listed on the IDX for 2017-2022 taken through purposive sampling. The method used in this research is panel data regression analysis using Eviews version 9. The results of this study indicate that the board of directors has a significant effect on financial performance, institutional ownership has a negative effect on financial performance